Поопераційний гіпотиреоз: сучасна оцінка та лікувальна тактика - Макар, Р. Д. (Clinical Endocrinology and Endocrine Surgery, 2009)
A thorough insight into the problem of postoperative hypothyroidism, development of its conception and contemporary position of the medical care are briefly reviewed.